Globalisasi Televisi Senjata Utama Neo-kolonialisme (Melihat Dominasi Negara Adikuasa Terhadap Negara Dunia Ketiga) - Filosa Gita Sukmono (LP3 UMY, 2015)
The globalization of television serves as an agent of the major powers to dominote the Third World countries; so that people in Third World countries become consumerist society. This tendency, then, will make capitalism easily going in and infiltrating those countries, because the market has been formed and created by television through a variety of impressions and entertaining as well as inf ormative programs.